Analysis, design and evaluation of quasi Z-Source modular multilevel converter - Khera, Fatma (2021)
The deployment of renewable energy production capability needs to increase significantly in the near future to be able to meaningfully reduce emissions caused by current electrical power generation. Also, the electrical energy and power generation will have to increase due to the need to decarbonize the transport which currently runs on fossil fuels. Recently, newly installed renewable energy production capabilities such as wind turbines and photovoltaics outpaced newly built fossil fuels generation capabilities. The voltage generated by these renewable energy sources often fluctuates in accordance with the weather conditions. Therefore, power converters are required to regulate the output voltage and maximize the available generated power. Technically speaking, available power converter solutions with both voltage step down and step-up capability are indispensable to maximise the capturing of renewable power. For this reason, the development of novel power converter topologies that could bring additional advantages to existing solutions is still under the scope. A new breed of multilevel converters, which is modular multilevel converter (MMC) which is able to be connected directly in medium and high voltage DC and AC networks, has been proposed and gained much attention. The MMC based on half-bridge sub-modules (HBSMs) is the simplest configuration but provides only voltage step-down conversion which is not sufficient for effective interfacing with many renewable energy sources. This thesis proposes the integration of the impedance networks especially quasi Z-source (qZS) network with the HBSM based modular multilevel converter (MMC). This integration has not previously been reported. The proposed quasi Z source modular multilevel converter (qZS-MMC) has the advantages of not only performing the commonly used voltage step down function but also voltage step up function. In addition, it was found that the proposed converter has an inherent capability to block the fault current during a DC side fault. The proposed qZS-MMC consists of two quasi Z-source networks inserted between the terminals of the input DC source and the DC-link terminals of a modular multilevel converter. The operation of the qZS-network requires the introduction of a short circuit at its output terminals in order to increase the energy stored in the qZS network inductors. This increase in the stored energy provides the converter’s voltage boosting capability. To provide the short circuit current path, each qZS-network is connected to a chain-link of series connected switches at its end terminals. By gating only one of these chain-links, the generated output voltage will be highly distorted. Therefore, two modulation techniques named simultaneously shorted (SS) and reduced inserted cells (RICs), are proposed to avoid any distortion in the output voltage. These techniques are analysed and compared based on a mathematical derivation for the converter internal voltages and currents. Based on these, guidelines for sizing the different passive components and a procedure for estimating the semiconductor losses are presented for each modulation technique. The DC-fault blocking capability of the proposed converter is investigated, where the converter behavior is illustrated for pole-to-pole and pole-to-ground DC side faults. The proposed qZS-MMC is compared with the full-bridge based MMC (FB-MMC) and quasi Z-source cascaded multilevel converter (qZS CMI) in order to validate its feasibility. The comparison accounts for the required number of the passive and active components, voltage and current stresses, the semiconductor power losses and output voltage waveform quality. The performance of the proposed converter is evaluated through simulation using PLECs software and different test cases were considered. The simulation results demonstrate the ability of the converter to perform buck-boost operation using the proposed modulation techniques and to block the DC-fault current. A laboratory scaled prototype is built and is used to experimentally validate the operation of the converter and the DC-fault blocking capability.